2019
DOI: 10.17844/jphpi.v22i3.29229
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Imported Commercial Fish Oils (Soft Gel) in East Java

Abstract: Commercial fish oils (soft gel) have been widely traded in Indonesia, especially in East Java.The aimof this research was to determine the quality and stability of fish oils (soft gel) in East Java examined bySchaal oven method and to determine the amount of fatty acids in the commercial fish oil. The stabilityof the commercial fish oil was determined based on peroxide value, anisidine value, and total oxidationafter the oils were stored at 40oC for 6 days. The experimental design used in this research was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Catfish (Pangasius hypophthalmus) is a source of unsaturated fatty acids, including omega-3 fatty acids, which have positive benefits for human health [12,13]. A previous study has shown that EPA and DHA content in catfish (Pangasius hypophthalmus) is higher than other freshwater fish [14][15][16][17]. EPA and DHA are known to have anti-inflammatory effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…Catfish (Pangasius hypophthalmus) is a source of unsaturated fatty acids, including omega-3 fatty acids, which have positive benefits for human health [12,13]. A previous study has shown that EPA and DHA content in catfish (Pangasius hypophthalmus) is higher than other freshwater fish [14][15][16][17]. EPA and DHA are known to have anti-inflammatory effects [18].…”
Section: Introductionmentioning
confidence: 99%